Hubungan antara Ukuran Karakteristik Saliva dan Kejadian Karies pada Anak Usia Sekolah Dasar Sasaran Program UKGS Binaan - Zaeni Dahlan; Tri Widyastuti; Isa Insanuddin (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2009)
Recent international studies have shown that saliva has some abilities to neutralize acidic situation in mouth, this ability is called as the saliva buffer capacity. In addition, saliva could influence tooth caries occurrence, which is because of that saliva is able to reduce of plaque accumulation on the tooth surface, and it therefore increases the carbohydrate cleansing from oral cavity. However little has known about salivary characteristics among school children and its relation to tooth decay.The objective of this research was to investigate the relationship between saliva characteristics, which are pH, the buffer capacity and saliva viscosity, and caries prevalence among school children in IJKGS program. The research method was analytical design with cross-sectional method classified as predictor study. The population was 1980 school children from some elementary schools implementing school based dental care programs organized by the Dental Health Department of Bandung Health Polytechnic. The study sample was 220 students chosen using the simple random sampling. The hypothesis testing was the multivariate regression linier analysis. The result has shown that there is a significant relation between pH of saliva and dental caries among school children (r = -0,666, p-value <0,001), while there is also a significant relation between the saliva buffer capacity and caries among school children (r = 0,588 p-value <0,001), however there is no significant relation between saliva viscosity and caries (r = 0,105, p value = 0,119). Simultaneously, there is a significant relation between three saliva characteristics and caries, which has shown by the value of multivariate coefficient correlation (R) that is 0.737. Meanwhile the value of Coefficient Determination (R-square) is 0.544, which explains that 54.4 % of changes in caries have been influenced by saliva characteristics.